Designing, physiochemical confirmation, evaluation of biological and in-silico potential of Triorganotin(IV) complexes - Hanifa, Bibi; Sirajuddin, Muhammad; Tiekink, Edward R.T.*; Khan, Ishaq; Kubicki, Maciej; Bari, Ahmed (Elsevier, 2022)
FTIR, NMR, CHN and single crystal X-ray crystallography were used to validate a series of three new triorganotin(IV) carboxylate complexes, R3Sn(L) for R=Methyl(1), n-Butyl(2) and Phenyl(3), obtained from LH=4-[(2,5-dimethoxyphenyl)carbamoyl]butanoic acid. The coupling constant and θC-Sn-C values in solution-state NMR data suggest a 5-coordinated environment around the Sn centre. In the crystal of 1, the carboxylate is bidentate bridging leading to a zigzag chain with the Sn centre having a distorted trigonal-bipyramidal geometry. The compounds were evaluated for their interaction with salmon sperm DNA and found that they interact through an intercalative mode resulting in hypochromism and bathochromic shift as confirmed by the UV-visible spectroscopic and viscometric techniques. The findings of anti-microbial activity performed on five bacterial and two fungus strains demonstrate that some of the compounds exhibit >80% inhibition of certain bacteria and >100% inhibition of certain fungal strains. The compounds were also evaluated for cell viability tested on human embryonic kidney cell (HEC-239) and human red blood cells (RBC). The anti-cancer potential of the compounds was assessed using cis-platin as a standard against human malignant glioma U87 (MG-U87) cell lines, and 1 was shown to be the most potent (IC50: 148.979 μM) at a 50μM dose. The DPPH anti-oxidant activity results revealed a 91% maximum scavenging activity for 1. The compounds follow the principles of drug-likeness and have good bioavailability potential, according to an in silico analysis conducted using the SwissADME webserver